1997
DOI: 10.1080/00914039708041023
|View full text |Cite
|
Sign up to set email alerts
|

The Fatigue Behaviour of Filled Epoxidized Natural Rubber Compounds

Abstract: The fatigue behaviour of white rice husk ash (WRHA) filled ENR-50 compounds was compared with those of silica (Vulcasil-S) and carbon black (N 330) filled compounds. The effect of WRHA loading on scorch time and Mooney viscosity was also studied. The incorporation of WRHA in ENR-50 compounds reduced the scorch time but increased the Mooney viscosity. The increment in filler loadings has resulted in the reduction of the fatigue life. The fatigue behaviour of ENR-50 vulcanizates was observed to be strain depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The introduction of llers into the matrix enhances stiffness, subsequently limiting molecular mobility. According to Ismail et al [54], incorporating llers at higher loading results in poorer ller dispersion and a decrease in the amount of rubber matrix that can be effectively wetted. This can act as a stress concentration, leading to a reduction in fatigue life.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of llers into the matrix enhances stiffness, subsequently limiting molecular mobility. According to Ismail et al [54], incorporating llers at higher loading results in poorer ller dispersion and a decrease in the amount of rubber matrix that can be effectively wetted. This can act as a stress concentration, leading to a reduction in fatigue life.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of wetted efficiency by rubber at higher loading of filler worsens the filler distribution in matrix. These inherent defects act as stress concentration and reduce the fatigue life 13, 14…”
Section: Resultsmentioning
confidence: 99%
“…However, less investigation regarding the effect of nanosize filler in fatigue properties has been done. Previously, many researchers have been used micrometer size of fillers such as paper sludge,12 white rice husk ash (WRHA),13, 14 feldspar,15 and oil palm wood flour16 to study the fatigue properties of rubber. From these investigations, all researchers stated that the addition of filler in rubber only caused reduction in fatigue life and increment in hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of HNTs increases the immobilization of rubber molecules, which induces stiffness in the nanocomposites. Mohd Ishak et al [22] stated that higher fatigue life is observed when the chains are more flexible, due to the higher resilience it has towards cyclic deformation. Hence, the reduction of flexibility shortens the fatigue life of nanocomposites.…”
Section: Fatigue Propertiesmentioning
confidence: 98%